In vitro antiviral activity of piperidine alkaloids from Senna spectabilis flowers on Chikungunya virus infection - Freitas, Thamires Rodrigues; Novais, Raul Marques; Santos, Igor Andrade; Martins, Daniel Oliveira Silva [UNESP]; Danuello, Amanda; da Silva Bolzani, Vanderlan [UNESP]; Jardim, Ana Carolina Gomes [UNESP]; Pivatto, Marcos (Springer Nature, 2022)
Background: Chikungunya fever is an endemic disease caused by the Chikungunya virus (CHIKV). To date there is no antiviral treatment against this infection or licensed vaccine to prevent it. Our study aims to evaluate whether (–)-cassine (1) and (–)-spectaline (2), the main alkaloids of Senna spectabilis, display anti-CHIKV activity. Both compounds have been described to be biologically active against neglected tropical diseases, including malaria, leishmaniasis, and schistosomiasis, which emphasizes that these molecules could be repurposed for chikungunya fever treatment. Methods: The structures of the isolated compounds 1 and 2 were identified by NMR and HRESIMS analyses, and their antiviral activity against CHIKV was assessed by a dose–response assay employing BHK-21 cells and CHIKV-nanoluc, a recombinant virus carrying the nanoluciferase gene reporter. Results: Compound 1 presented CC50 of 126.5 µM and EC50 of 14.9 µM, while compound 2 presented CC50 of 91.9 µM and EC50 of 8.3 µM. The calculated selectivity index (SI) was 8.5 for 1 and 11.3 for 2. Conclusion: The data presented herein show that compounds 1 and 2 have potential for being repurposed as anti-CHIKV drug. Our promising in vitro results encourage further in vitro and in vivo assays. This is the first description of the antiviral activity of compounds 1 and 2 against CHIKV infection, which can impact the development of antiviral drug candidates against chikungunya fever, which sometimes can be debilitating. Graphical Abstract: [Figure not available: see fulltext.]
Keywords: Antiviral; Chikungunya fever; Chikungunya virus; Fabaceae; Neglected tropical diseases; Piperidine alkaloids; Senna spectabilis